2023
DOI: 10.1021/jacsau.2c00621
|View full text |Cite
|
Sign up to set email alerts
|

Silicalite-1 Layer Secures the Bifunctional Nature of a CO2 Hydrogenation Catalyst

Abstract: Close proximity usually shortens the travel distance of reaction intermediates, thus able to promote the catalytic performance of CO 2 hydrogenation by a bifunctional catalyst, such as the widely reported In 2 O 3 /H-ZSM-5. However, nanoscale proximity (e.g., powder mixing, PM) more likely causes the fast deactivation of the catalyst, probably due to the migration of metals (e.g., In) that not only neutralizes the acid sites of zeolites but also leads to the reconstruction of the In 2 O 3 surface, thus resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In fact, a general strategy for constructing spatially segregated multiple metallic components in a zeolite catalyst for the increasing modern demands is strongly desired. Recently, Arian 18 disclosed the epitaxial growth rules of silicalite-1 over ZSM-5, and the obtained results confirmed the growth of an epitaxial silicalite-1 layer without blocking the pore permeability of the inner zeolite core and the catalyst exhibited excellent catalytic performance.…”
mentioning
confidence: 79%
“…In fact, a general strategy for constructing spatially segregated multiple metallic components in a zeolite catalyst for the increasing modern demands is strongly desired. Recently, Arian 18 disclosed the epitaxial growth rules of silicalite-1 over ZSM-5, and the obtained results confirmed the growth of an epitaxial silicalite-1 layer without blocking the pore permeability of the inner zeolite core and the catalyst exhibited excellent catalytic performance.…”
mentioning
confidence: 79%
“…Indium oxide (In 2 O 3 ) and In 2 O 3 -supported catalysts have attracted extensive attention for CO 2 hydrogenation reactions. Partially reduced In 2 O 3 with rich surface oxygen vacancies is highly active but suffers from over-reduction and sintering in the H 2 -containing atmospheres. It is a crucial but challenging task to achieve highly dispersed CUSs of In 2 O 3 confined on supports, and they have high activity and stability. Herein, we present a study on the interface confinement effect in an In 2 O 3 –TiO 2 catalyst during the reverse water gas shift (RWGS) reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Different metals exhibited different reducibility and migratability under reaction conditions, as reported by Wang et al and Ding et al For example, In and Zn are easily reduced and migrate into zeolite forthwith neutralizing partial BASs; on the contrary, the migration ability of Cr, Zr, and Mn is relatively weak. Xing et al recently found the S-1 layer on the HZSM-5 surface is an efficient shield for defending In migration.…”
Section: Introductionmentioning
confidence: 99%